Careers Guidance and Transitions to Further Education in Wales - Huxley, Katy; Davies, Rhys; Yunus, Suhaer (International Journal of Population Data Science, 2019)
There is a general agreement that receiving appropriate and timely careers guidance enhances the likelihood of an individual’s participation in post-compulsory education. However, little is understood about how careers guidance influences the choices of learners. This paper explores the educational journey of learners’ who enrol within the Further Education sector in Wales, analysing whether the receipt of careers guidance is in anyway associated with these outcomes. This study utilises the linked database of school and pupil records, combining information from the Welsh National Pupil Database (NPD) with individual learner records from the Lifelong Learning Wales Record (LLWR) for young people who are registered at post-compulsory education providers, combined with anonymised client information held by Careers Wales. Data for two cohorts of Year 11 pupils (2012/13 and 2013/14) who subsequently enrolled in courses within the FE sector during the following academic year is analysed. Multivariate analysis reveals that, as expected, there is a strong link between GCSE attainment and learning aims at FE. However, the analysis also suggests that receipt of careers guidance may encourage learners to make choices at FE that are more commensurate with their abilities. Those with higher levels of attainment are also more likely to enrol on higher level learning programmes if they have also been in receipt of careers guidance. Likewise, those with low levels of attainment at GCSE are more likely to enrol on learning programmes with lower qualification aims if they have been in receipt of careers guidance. Receiving careers guidance through interviews increased the likelihood of registering on WBL programmes. Furthermore, learners on WBL programmes who have received careers guidance are less likely to withdraw from their courses early. The study offers important insights as to the role of career guidance in supporting young people in their transitions to post-compulsory education.